PENENTUAN JENIS KELAMIN BULU BABI Tripneustes gratilla SECARA MORFOLOGI - Abdul Hamid A. Toha; Agung Pramana; Sutiman B. Sumitro; Luchman Hakim; Widodo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
Determining the sex of T. gratilla was difficult and generally determined directly by the presence, length and shape as well as size gonopore genital papilla. We tried to determine of the gender 17 individual of T. gratilla based on morphological approach. Injection of KCl and cleavage of the whole individual is also carried out to observe the color of the gonads as a reference for determining the sex. We found 6 samples of female and 11 male samples based on gonad color. The results of morphological measurements showed that all parameters used have not been able to determine the sex of T. gratilla, either singly or in combination parameters. The number of samples need to be added till at least 30 individual each sex. This is consistent with logistic regression 3, where the P-value is less than the P-value logistic regression 1 and 2, which enables different results if the sample size is enlarged.